The Pathogenesis and Surgical Nursing of Coronary Heart Disease (CHD) - Yan, Ran (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Coronary Heart Disease (CHD) stands as a significant global health concern, being the leading cause of mortality worldwide. This paper delves into the multifaceted aspects of CHD, exploring its pathogenesis, clinical manifestations, and treatment modalities, with a particular focus on coronary artery bypass graft (CABG) surgery. The pathogenesis of CHD is complex, involving factors such as atherosclerosis, cognitive dysfunction, cerebral small vessel disease, high platelet activation, and chronic inflammation. Clinical symptoms range from insidious presentations to acute coronary syndrome and sudden death. CABG, a pivotal intervention, is discussed extensively, covering preoperative assessments, intraoperative procedures, and postoperative care. Both on-pump and off-pump CABG techniques are examined in detail, highlighting their respective benefits and risks. Postoperative care involves meticulous monitoring and management to ensure optimal recovery. Additionally, strategies for the clinical enhancement of prevention are outlined, emphasizing lifestyle modifications and risk factor management. This comprehensive exploration aims to deepen understanding, stimulate further research, and guide clinical practice in combating CHD.